Parasitoid of cassava mealybug, Anagyrus lopezi (Hymenoptera: Encyrtidae): Mummy size, adult emergence, sex ratio, and parasitization level - Fatayatun Naimah; Dewi Sartiami; Nina Maryana; Ruly Anwar; Pudjianto Pudjianto (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Naimah F, Sartiami D, Maryana N, Anwar R, Pudjianto. 2023. Parasitoid of cassava mealybug, Anagyrus lopezi (Hymenoptera: Encyrtidae): mummy size, adult emergence, sex ratio, and parasitization level. Biodiversitas 24: 1629-1634. The presence of Anagyrus lopezi as a natural enemy can reduce the population of Phenacoccus manihoti. This parasitoid was introduced from Thailand to Indonesia in 2014 to control cassava mealybugs. This research aims to determine the mummy length and width, adult emergence time, sex ratio, and parasitization level. This study was conducted in July-November 2022, while parasitoids and mealybugs were obtained from Bogor, Indonesia. The size of mummies was measured under Dino-light digital microscope; the emergence time was counted for 24 hours within six days, and the sex ratio of parasitoids was calculated based on the number of males and females emergence. The parasitization level was observed from four female parasitoids at 120, 160, and 200 of host population densities. The study showed the length and width of female mummies (n: 100) were 0.71 mm and 1.64, while the length and width of male mummies (n: 100) were shorter than female with 1.00 mm and 2.18 mm. The peak time of adult emergence is A. lopezi, i.e., during the daytime at 09:01-12:00 AM and 03:01-06:00 PM. The sex ratio of parasitoids from the field and laboratory was 1:0.49, 1:1.05, and 1:1.09, respectively. The one-way ANOVA and Tukey's test at a 5% significance level showed that the host population density of 120 nymphs was significantly different from other densities, with a parasitization level of 66.7%.